Photocatalytic Anaerobic Oxidation of Aromatic Alcohols Coupled With H2 Production Over CsPbBr3/GO-Pt Catalysts - Chen, Taoran; Li, Mengqing; Shen, Lijuan; Roeffaers, Maarten B. J.; Weng, Bo; Zhu, Haixia; Chen, Zhihui; Yu, Dan; Pan, Xiaoyang; Yang, Min-Quan; Qian, Qingrong (Frontiers in Chemistry, 2022)
Metal halide perovskites (MHPs) have been widely investigated for various photocatalytic applications. However, the dual-functional reaction system integrated selective organic oxidation with H2 production over MHPs is rarely reported. Here, we for the first time demonstrate the selective oxidation of aromatic alcohols to aldehydes integrated with hydrogen (H2) evolution over Pt decorated CsPbBr3. Especially, the functionalization of CsPbBr3 with graphene oxide (GO) further improves the photoactivity of the perovskite catalyst. The optimal CsPbBr3/GO-Pt exhibits a H2 evolution rate of 1060 μmol g−1 h−1 along with high selectivity (> 99%) for benzyl aldehyde generation (1050 μmol g−1 h−1) under visible light (λ > 400 nm), which is about 5 times higher than CsPbBr3-Pt sample. The enhanced activity is ascribed to two effects induced by GO introduction; (i) GO displays a structure-directing role, decreasing the CsPbBr3 particle size; and (ii) GO and Pt acts as electron reservoir, extracting the photogenerated electrons and prohibiting the recombination of the electron-hole pairs. This study opens new avenues to utilize metal halide perovskites as dual-functional photocatalysts to perform selective organic transformations coupled to solar fuel production.